2018
DOI: 10.1017/s0007114518001617
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic perturbations associated with the consumption of a ketogenic medium-chain TAG diet in dogs with idiopathic epilepsy

Abstract: Consumption of diets containing medium-chain TAG (MCT) has been shown to confer neuroprotective effects. We aim to identify the global metabolic perturbations associated with consumption of a ketogenic diet (medium-chain TAG diet (MCTD)) in dogs with idiopathic epilepsy. We used ultra-performance liquid chromatography-MS (UPLC-MS) to generate metabolic and lipidomic profiles of fasted canine serum and made comparisons between the MCTD and standardised placebo diet phases. We identified metabolites that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…The influence of dietary modification on seizure control has been extensively studied in human medicine 26‐29 and rodent epilepsy models, 30‐33 showing antiseizure effects to varying degrees. Similarly, there are effects of nutritional management and diets in dogs with epilepsy 23,24,34‐39 and paroxysmal dyskinesia 40‐43 …”
Section: Introductionmentioning
confidence: 99%
“…The influence of dietary modification on seizure control has been extensively studied in human medicine 26‐29 and rodent epilepsy models, 30‐33 showing antiseizure effects to varying degrees. Similarly, there are effects of nutritional management and diets in dogs with epilepsy 23,24,34‐39 and paroxysmal dyskinesia 40‐43 …”
Section: Introductionmentioning
confidence: 99%
“…It was not a "ketogenic" diet, and thus may be less effective for some dogs than it was for Case 2. [13][14][15] The need for alternatives to current AEDs in dogs is underscored by their lack of efficacy in some cases and harmful side effects in others, 4 including-as detailed in Case 1's report-liver damage from prolonged use of phenobarbital. Anecdotally, Case 1's owners also reported that while in the process of researching his condition and customizing his diet, ingestion of a nonketogenic treat seemed to trigger a seizure event.…”
Section: Discussionmentioning
confidence: 99%
“…The diet-related improvements noted here are consistent with previous reports-including a randomized studyshowing that changes in diet can reduce seizures and improve behavior. [13][14][15] The need for alternatives to current AEDs in dogs is underscored by their lack of efficacy in some cases and harmful side effects in others, 4 including-as detailed in Case 1's report-liver damage from prolonged use of phenobarbital. In addition, AEDs can have adverse behavioral effects, as observed prominently in Case 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations